The effectiveness of real-time haptic feedback gait retraining for reducing resultant tibial acceleration with runners - Sheerin, K. R.; Reid, D.; Taylor, D.; Besier, T. F. (Physical Therapy in Sport, 2020)
Objectives: To examine the effectiveness of real-time haptic feedback gait retraining for reducing resultant tibial acceleration (TA-R) with runners, the retention of changes over four weeks, and the transfer of learning to overground running. Design: Case control. Setting: Biomechanical laboratory treadmill, and track-based overground, running. Participants: 18 experienced uninjured high tibial acceleration runners. Main outcome measures: TA-R measured while treadmill and overground running assessed at pre-, post- and 4-weeks post-intervention. Results: Across the group, a 50% reduction in TA-R was measured post-intervention (ES: 0.9, z = -18.2, p < .001), and 41% reduction at 4-weeks (ES: 0.8, z = -12.9, p < .001) with treadmill running. A 28% reduction (ES: 0.7, z = -13.2, p < .001), and a 17% reduction in TA-R were measured at these same time points when runners ran overground (ES: 0.7, z = -11.2, p < .001). All but two runners responded positively to the intervention at the post-intervention assessment. Eleven runners were categorised as positive responders to the intervention at the 4-week post-intervention. Conclusions: Haptic feedback based on TA-R appears to be as effective, but less invasive and expensive, compared to other more established modalities, such as visual feedback. This new approach to movement retraining has the potential to revolutionise the way runners engage in gait retraining.